1996
DOI: 10.7326/0003-4819-124-9-199605010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized Prostacyclin and Iloprost in Severe Pulmonary Hypertension

Abstract: Aerosolization of prostacyclin or its stable analog iloprost causes selective pulmonary vasodilatation, increases cardiac output, and improves venous and arterial oxygenation in patients with severe pulmonary hypertension. Thus, it may offer a new strategy for treatment of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
200
2
22

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(234 citation statements)
references
References 0 publications
10
200
2
22
Order By: Relevance
“…12 When administered during a short aerosolization ma-neuver to patients with pulmonary hypertension, its pulmonary vasodilative potency was similar to that of prostacyclin, but its effects lasted for 30 to 90 minutes, as compared with 15 minutes. 4,11,[13][14][15] Several open-label, uncontrolled studies of patients with severe pulmonary hypertension suggested that longterm use of aerosolized iloprost results in substantial clinical improvement. 11,13,[16][17][18][19][20] Our objective in this trial was to evaluate the effects of inhaled iloprost using a rigorous end point of clinical efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 When administered during a short aerosolization ma-neuver to patients with pulmonary hypertension, its pulmonary vasodilative potency was similar to that of prostacyclin, but its effects lasted for 30 to 90 minutes, as compared with 15 minutes. 4,11,[13][14][15] Several open-label, uncontrolled studies of patients with severe pulmonary hypertension suggested that longterm use of aerosolized iloprost results in substantial clinical improvement. 11,13,[16][17][18][19][20] Our objective in this trial was to evaluate the effects of inhaled iloprost using a rigorous end point of clinical efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Postinhalation assessments of hemodynamic variables demonstrated a significant improvement in the iloprost group, as was anticipated on the basis of previous reports. 4,11,13,16 Since the acute hemodynamic response did not differ between the groups, it appears unlikely that tolerance developed over the 12-week course of iloprost treatment. During long-term treatment, the patients' hemodynamic status is somewhere between preinhalation and postinhalation values.…”
Section: Discussionmentioning
confidence: 99%
“…Treprostinil is a potent IP receptor agonist (7), although its specificity for this receptor is unknown. Iloprost (8) is an inhaled prostacyclin analog with a half-life between those of epoprostenol and treprostinil that was also approved by the FDA for use in PAH. Though iloprost is a potent IP receptor agonist that is commonly used in vitro, it also demonstrates significant binding to two of the four E prostanoid (EP) receptors, namely the G ␣q -coupled EP1 and the G ␣i -coupled EP3 subtypes (9).…”
Section: Synthetic Prostacyclin Analogs Differentially Regulate Macromentioning
confidence: 99%
“…10 The advantages of inhaled PGI 2 and iloprost include a lack of toxic reactions and ease of administration. 7,11 On the other hand, Haraldsson et al found no improved effects on hemodynamic variables, comparing inhaled PGI 2 with inhaled NO in the evaluation of heart transplant candidates. 6 Currently, there exists little information regarding the use of milrinone by inhalation.…”
Section: Objectifmentioning
confidence: 99%